Enhancing environmental performance through green HRM and green innovation: Examining the mediating role of green creativity and moderating role of green shared vision - Muhammad Siddique Malik; Kamran Ali; Naila Kausar; Muhammad Amir Chaudhry (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
Organizations encourage green creativity among workers to mitigate pollution and achieve sustainable growth. Green human resource management (GHRM) activities have a welldocumented role in influencing workers' green attitudes and environmental efficiency. The aim of this research is to see how Green HRM activities affect employee green innovation. Furthermore, the mediating influence of green creativity between the association of GHRM and green innovation is explored. Moderation of green shared vision between the association of green innovation and environmental performance is also investigated. In this analysis, we used SPSS and AMOS software to run structural equation modeling to test study hypotheses. For hypothesis testing, data was obtained from 437 employees employed in a variety of industries of Pakistan. Results show that GHRM has a positive and significant influence on green creativity and green innovation. Moreover, green creativity significantly mediates the association between GHRM and green innovation. It means that GHRM can not only directly affect green innovation, but also indirectly influence it via green creativity. Moreover, this study also explores that the significant positive association between green innovation and environmental performance is moderated by green shared vision. This study adds the indicator of green creativity as one of the key antecedents of green innovation and environmental performance to the previous literature. Furthermore, this study contributes to the prior literature by using green shared vision as a moderator between green innovation and environmental performance. Overall, findings of this study support all direct and indirect hypotheses and have several theoretical and practical implications for top management and policymakers to ensure employee commitment to GHRM practices and green innovation implementation in order to achieve high environmental performance.
Keywords: 330; green human resource management; green creativity; green innovation; greenshared vision; environmental performance